2017
DOI: 10.1016/j.msea.2017.05.115
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and mechanical properties of an as-cast Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr alloy processed by high pressure torsion

Abstract: Abstract:The novel Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr alloy with high content of rare earth elements has been processed successfully by high pressure torsion (HPT) starting from an as-cast condition. HPT processing was conducted at room temperature for a range of turns from 1/8 to 16, and the evolutions of microstructure and microhardness were investigated.The average grain size decreases from ~85 μm in the as-cast condition to ~55 nm when the equivalent strain reaches ~6.0, and remains almost constant on further strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Thus, the solute content of the α-Mg remains reasonably constant and causes no supplementary hardening. There is evidence for such solution hardening in an Mg-Gd-Y-Zn-Zr alloy after HPT processing [68]. Furthermore, this research also revealed a mechanism of dispersion hardening by which the Mg-RE intermetallics in the Mg-Gd-Y-Zn-Zr alloy were broken into small particles with sizes of ~1-10 μm and were then homogeneously dispersed in the matrix after HPT for 16 turns [68].…”
Section: Hardness Evolutionmentioning
confidence: 67%
“…Thus, the solute content of the α-Mg remains reasonably constant and causes no supplementary hardening. There is evidence for such solution hardening in an Mg-Gd-Y-Zn-Zr alloy after HPT processing [68]. Furthermore, this research also revealed a mechanism of dispersion hardening by which the Mg-RE intermetallics in the Mg-Gd-Y-Zn-Zr alloy were broken into small particles with sizes of ~1-10 μm and were then homogeneously dispersed in the matrix after HPT for 16 turns [68].…”
Section: Hardness Evolutionmentioning
confidence: 67%
“…Amongst SPD techniques, high pressure torsion (HPT) processing has the potential for achieving the greatest grain refinement at room temperature by using extremely large torsional straining and high hydrostatic pressure to prevent cracking. SPD has also been applied to refine and disperse second phases effectively in different alloys, such as Mg alloys, Al alloys and pearlitic steels [21][22][23][24]. The evolution of the second phase particles during SPD depends on various factors such as their size, morphology and also the processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain strong age hardening effect, a multi-element Mg-Y-Gd-Zn-Zr alloy was employed. This alloy system has been proved to exhibit obvious aging effect by various precipitates and contains LPSO phase as well, which showed great potential for industrial applications as a promising high-performance magnesium alloy [23,32,33]. In the present work, we prepared an UFG Mg-10Y-6Gd-1.5Zn-0.5Zr alloy via multi-pass ECAP first and then comparatively investigated the effects of two kinds of aging treatments (T5 and T6) on precipitation behaviors, microstructure evolutions and mechanical properties of the UFG alloy.…”
Section: Introductionmentioning
confidence: 99%